2001
DOI: 10.1093/fampra/18.4.383
|View full text |Cite
|
Sign up to set email alerts
|

New-onset palpitations in general practice: assessing the discriminant value of items within the clinical history

Abstract: This study provides some information on the characteristics of patients reporting palpitations to GPs who may have 'significant' cardiac arrhythmias. Based on this work, we believe that a larger community-based study would be worthwhile and would provide useful and useable clinical discriminant information for GPs in the settings where they work and amongst the types of patients they encounter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
0
29
1
3
Order By: Relevance
“…Similar observations were found in a study by Summerton et al which showed palpitations during exertion had cardiac aetiology. 5 Associated symptoms of palpitation were chest pain, shortness of breath and syncope. Chest pain was encountered in 9 % and shortness of breath was present in 17 % of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were found in a study by Summerton et al which showed palpitations during exertion had cardiac aetiology. 5 Associated symptoms of palpitation were chest pain, shortness of breath and syncope. Chest pain was encountered in 9 % and shortness of breath was present in 17 % of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In Summerton study, involving patients with new onset palpitations in general practice, 19% of patients had significant cardiac arrhythmia. [6] In Chu study, involving patients in a regional Accident and Emergency Department of Hong Kong arranged for Holter monitoring, 16.7% of patients presented with palpitation were found to have significant cardiac arrhythmia. [11] Around 2,688 patients underwent Holter monitoring for investigation of palpitation in Sreenkumar study, the commonest two findings were 6.6% paroxysmal atrial fribrillation (PAF) and 4.4% frequent ectopics.…”
Section: Discussionmentioning
confidence: 99%
“…[6] " New onset" palpitation referred to patient's symptom(s) had occurred within 3 months preceding the first visit to the clinic. Patient who had a history of previous episodes of palpitation or palpitation had occurred more than 3 months was defined as "old" symptom.…”
Section: Definition and Holter Monitoringmentioning
confidence: 99%
See 2 more Smart Citations